Răspuns:
Ex14
A) a=
[tex] \sqrt{3} - 1 + 4 - \sqrt{3} [/tex]
[tex] - 1 + 4 = 3[/tex]
[tex]b = \frac{2}{2 + 2 \sqrt{2} + 1 } + 4 + 4 \sqrt{2} + 2[/tex]
[tex] b = \frac{2}{3 + 2 \sqrt{2} } + 4 + 4 \sqrt{2} + 2[/tex]
[tex]b = 2(3 - 2 \sqrt{2} ) + 4 + 4 \sqrt{2} + 2 [/tex]
[tex]b = 6 - 4 \sqrt{2} + 4 + 4 \sqrt{2} [/tex]
[tex]b = 6 + 4 + 2[/tex]
[tex]b = 12[/tex]
B)
[tex]a = 3 \sqrt{2} + \sqrt{5} - \sqrt{18} + 1[/tex]
[tex]a = 3 \sqrt{2} + \sqrt{5} - 3 \sqrt{2} + 1[/tex]
[tex]a = \sqrt{15} + 1[/tex]
[tex] b = \sqrt{7} - \sqrt{5} - ( \sqrt{7} - 2 \sqrt{5} ) - 1[/tex]
[tex] \sqrt{7} - \sqrt{5} - \sqrt{7} + 2 \sqrt{5} + 1[/tex]
[tex] - \sqrt{5} + 2 \sqrt{5 - 1} [/tex]
[tex]b = \sqrt{5} - 1[/tex]